Effects of buffer compensation strategies on the electrical performance and RF reliability of AlGaN/GaN HEMTs. Issue 9 (August 2015) - Bisi, D.; Stocco, A.; Rossetto, I.; Meneghini, M.; Rampazzo, F.; Chini, A.; Soci, F.; Pantellini, A.; Lanzieri, C.; Gamarra, P.; Lacam, C.; Tordjman, M.; et al.
Abstract: The effects of buffer compensation strategies on the electrical performance and RF reliability of AlGaN/GaN HEMTs have been studied by means of static and dynamic I–V measurements, drain-current transient spectroscopy, XRD, and RF stress tests. Devices equipped with C-doped and Fe-doped GaN buffer feature improved subthreshold behaviour (lower source-to-drain leakage current, and lower DIBL) and improved RF reliability. As a drawback, devices equipped with Fe- and C-doping experience higher dynamic current dispersion, ascribed to higher concentration of the deep levels E2 (0.56 eV/10 − 15 cm 2 ) and E4 (0.84 eV/10 − 14 cm 2 ). Highlights: Buffer compensation studied by means of static and dynamic I-V, DCTS, XRD, and rf stress tests. Devices equipped with C-doped and Fe-doped GaN buffer feature improved subthreshold behaviour and improved RF reliability. Devices equipped with Fe- and C-doping experience higher dynamic current dispersion.